Indicators of compliance with the standard in environmental preservation and conservation of vegetation in areas of land reform settlement - Maria Alice Cruz Alencastro (2007)
The use of the natural resources have been an essential element for the development and reproduction of the human life in the Earth. The expression âsustainable developmentâ, that appeared during the global environmental events that took place in the 1970Âs, beggined to be used as a support to the solidification procedure of a new paradigm in the society-nature relations, intenting to behave a development procedure led by social, economic and ecological objetives, as a way to fetch the human life quality. The enviromental law appeared in this context as a tool to regulate the relations among man and the natural resources. If the brazilian environmental law had a great advance in the increasing of the norms quantity since the second half of XX century, nowadays the efforts are related to obtain tools to evaluate and effective their compliance and enforcement. Considering the relevance and the sustainable development assimilation procedure in the National Program of Agrarian Reform, this paper aimed to propose and to apply a sistem of indicators to measure the compliance with the environmental law â related to the vegetation conservation and/or preservation in agrarian reform areas. The paper also aimed to apply variables to identify the social, economic and institutional characteristics of the agrarian reform areas. The indicadors were classified in 5 groups and were tested at the Coqueirinho area, settled at Fortim, CearÃ. The indices related to each group of indicators were used to build the indice of compliance with environmental law (ICNA). The value obtained for the ICNA expressed a low level of compliance with the environmental rules at the study area. The variables allowed to identify factors related to the life quality of the familiesÂ area that also could stimulate the compliance or non-compliance with the environmental law. The indicators were an usefull tool to evaluate the compliance with the environmental law for vegetation, to simplify data that can be compared in a future time and also to identify priorities programmes to estimulate the community to comply with environmental laws.